META ANALISIS : EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL TERHADAP HASIL BELAJAR SISWA TINGKAT SEKOLAH DASAR - Laily Rohmatin Suhardi; M. Zainudin (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
We have often heard of meta-analytical research related to digital learning media, but this time the research wants to research related to digital learning media with its novelty form. This meta-analyzing study was conducted with the aim of knowing the total effect size and analyzing digital learning media on learning outcomes, where this meta-analysis research used 9 research articels from 970 scirntific articles found on Harzing’s Publish or Peerish platforms that met the exclusion and inclusion criteria. The results of the meta-analysis showed that digital learning media on learning outcomes for its application was more effective at the elementary level with the help of Geoboard media as evidenced by the high effect size value of 1,6036.Keywords: digital learning media, learning outcomes, elementary level